Alloy soft magnetic composite material with core-shell structure as well as preparation method and application of alloy soft magnetic composite material

By using a core-shell structure alloy soft magnetic composite material in the ferrosilicon aluminum magnetic powder core, the core material composition and doped heteroatomic elements are adjusted, and the passivation layer and insulating coating are added, the problem of increasing magnetic loss in high-temperature environments is solved. , achieving more efficient inductance performance and stability.

CN119132779APending Publication Date: 2024-12-13HENGDIAN GRP DMEGC MAGNETICS CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411363312.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The existing ferrosilicon aluminum metal magnetic powder core has increased magnetic loss in high temperature environments, resulting in a decrease in efficiency. The existing coating technology has poor thermal conductivity, which is easy to destroy the thermal balance.

Method used

Using alloy soft magnetic composite materials with core-shell structure, by adjusting the alloy soft magnetic core material composition and doping with heteroatomic elements, the passivation layer and insulating coating layer are increased, and the anisotropic field and insulation performance of magnetic crystals are improved, and the insulating performance is reduced. High temperature loss.

Benefits of technology

It effectively reduces the total loss of alloy soft magnetic composite materials at high temperatures, improves the power stability and production efficiency of the device, and extends the service life within the operating temperature range.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005065454240000091
    Figure BDA0005065454240000091
  • Figure BDA0005065454240000101
    Figure BDA0005065454240000101
  • Figure BDA0005065454240000121
    Figure BDA0005065454240000121
Patent Text Reader

Abstract

The invention provides an alloy soft magnetic composite material with a core-shell structure as well as a preparation method and application of the alloy soft magnetic composite material. The alloy soft magnetic composite material with the core-shell structure sequentially comprises a modified alloy soft magnetic core material, a passivation layer and an insulating coating layer from inside to outside, the modified alloy soft magnetic core material is an alloy soft magnetic core material doped with heteroatom elements. The invention provides the alloy soft magnetic composite material which has lower loss when being used at high temperature, so that the prepared device has good power stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of soft magnetic materials, and in particular relates to an alloy soft magnetic composite material with a core-shell structure and a preparation method and application thereof. Background Art

[0002] Inductors are one of the three most important basic components in modern electronic circuits. They play important roles in filtering, isolation, and energy storage. With the development of semiconductor materials, the frequency of all devices in the circuit has doubled, which puts higher requirements on basic components, especially inductors, which are most affected by frequency. Because their components contain soft magnetic materials that are particularly sensitive to frequency, when the frequency increases by 1 times, the corresponding magnetic loss increases by 2 to 4 times. The proportion of new inductors with soft magnetic metal powder cores as inductor cores in circuits subjected to high current environments is gradually increasing. However, the metal core has a low resistance and is easily excited by current to produce high temperatures, which affects its efficiency when used in high temperature environments.

[0003] Sendust metal powder core has the lowest loss (Pcv≤150mW / cm2 at 100kHz, 100mT) 3 ) and is widely used in the manufacture of various electronic components. However, during use, the internal part of the metal gradually heats up, causing its magnetic loss to further increase. If the temperature of the magnetic core exceeds its operating temperature range, the soft magnetic properties of the sendust metal material may drop rapidly or even be completely lost. Therefore, a method or means is needed to suppress the further increase of the magnetic loss of the sendust metal material at high temperatures.

[0004] At present, most of the Sendust metal powder cores are a kind of composite soft magnetic material formed by mixing ferromagnetic metal powder with insulating agent and adhesive. Its own thermal conductivity directly affects the accumulation speed of magnetic loss inside, thereby accelerating or delaying the material's near working temperature. For example, the prior art discloses the use of silicone resin to coat the Sendust metal powder core to increase its adhesion, but the coating is easy to decompose during the annealing process, and the internal gap of the magnetic core is too large, resulting in poor thermal conductivity and easy destruction of the inductor thermal balance. Based on this, Chinese patent CN111696744A discloses the use of silicone modified epoxy resin + oxidized powder to insulate and coat metal powder to make a high-stacked Sendust magnetic powder core, which can effectively solve the molding problem and high-temperature annealing problem, but it still does not involve how to reduce the magnetic loss of the Sendust metal powder core in a high-temperature working environment.

[0005] Therefore, in the art, there is an urgent need to develop a Sendust metal magnetic powder core material to solve the above problems. Summary of the invention

[0006] In view of the shortcomings of the prior art, the purpose of the present invention is to provide an alloy soft magnetic composite material with a core-shell structure and a preparation method and application thereof. The present invention provides an alloy soft magnetic composite material with lower loss when used at high temperatures, so that the prepared device has good power stability.

[0007] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0008] In a first aspect, the present invention provides an alloy soft magnetic composite material with a core-shell structure, wherein the alloy soft magnetic composite material with a core-shell structure comprises, from inside to outside, a modified alloy soft magnetic core material, a passivation layer, and an insulating coating layer;

[0009] The modified alloy soft magnetic core material is an alloy soft magnetic core material doped with heteroatom elements.

[0010] On the one hand, the present invention adjusts the specific composition of the alloy soft magnetic core material and uses heteroatom elements for doping to change the anisotropy field of the magnetic crystal, thereby improving the inductance (magnetic permeability) working temperature of the alloy soft magnetic material, and ultimately changing the trend of the high-frequency eddy current loss of the ordinary alloy soft magnetic powder core increasing with the increase of the working temperature, so that it has lower eddy current loss and hysteresis loss at a higher working temperature, thereby maintaining the overall efficiency of the prepared device at a higher level; on the other hand, the present invention uses materials with good high temperature resistance and insulation to insulate and coat the alloy soft magnetic core material respectively, so that the alloy soft magnetic composite material is easy to form, thereby realizing the preparation of high temperature resistant, low-loss alloy magnetic powder core, and ultimately effectively reducing the total loss at high temperature, changing its trend of increasing loss after the working temperature rises, thereby ensuring the efficiency of the prepared device.

[0011] The high temperature resistant and insulating material provided by the present invention has good compatibility with the modified alloy soft magnetic core material, and the preparation process is simple and the operation is convenient, thereby improving the production efficiency of the alloy soft magnetic composite material.

[0012] Preferably, based on the total mass of the modified alloy soft magnetic core material as 100%, the modified alloy soft magnetic core material includes 84.0wt.% to 85.5wt.% of iron element, 7.4wt.% to 9.4wt.% of silicon element, 6wt.% to 6.8wt.% of aluminum element and 0.1wt.% to 0.2wt.% of heteroatom elements in mass percentage respectively, preferably 84.4wt.% to 84.5wt.% of iron element, 9.4wt.% of silicon element, 6% of aluminum element and 0.2wt.% of heteroatom elements.

[0013] In the present invention, the mass percentage of the iron element is 84.0wt.% to 85.5wt.%, for example, it can be 84.0wt.%, 84.1wt.%, 84.2wt.%, 84.3wt.%, 84.4wt.%, 84.41wt.%, 84.42wt.%, 84.43wt.%, 84.44wt.%, 84.45wt.%, 84.46wt.%, 84.47wt.%, 84.48wt.%, 84.49wt.%, 84.5wt.%, 84.6wt.%, 84.7wt.%, 84.8wt.%, 84.9wt.%, 85.0wt.%, 85.2wt.%, 85.5wt.%, etc.

[0014] In the present invention, the mass percentage of the silicon element is 7.4wt.% to 9.4wt.%, for example, it can be 7.4wt.%, 7.5wt.%, 7.6wt.%, 7.7wt.%, 7.8wt.%, 7.9wt.%, 8.0wt.%, 8.2wt.%, 8.4wt.%, 8.6wt.%, 8.8wt.%, 9.0wt.%, 9.1wt.%, 9.2wt.%, 9.3wt.%, 9.4wt.%, etc.

[0015] In the present invention, the mass percentage of the aluminum element is 6wt.% to 6.8wt.%, for example, it can be 6wt.%, 6.1wt.%, 6.2wt.%, 6.3wt.%, 6.4wt.%, 6.5wt.%, 6.6wt.%, 6.7wt.%, 6.8wt.%, etc.

[0016] In the present invention, the mass percentage of the heteroatom elements is 0.1wt.% to 0.2wt.%, for example, it can be 0.1wt.%, 0.11wt.%, 0.12wt.%, 0.13wt.%, 0.14wt.%, 0.15wt.%, 0.16wt.%, 0.17wt.%, 0.18wt.%, 0.19wt.%, 0.2wt.%, etc. The present invention adjusts the mass percentage of the heteroatom elements so that the anisotropy coefficient of the alloy soft magnetic crystal is close to zero. If the mass percentage of the heteroatom elements is low, the anisotropy coefficient of the alloy soft magnetic crystal will increase, otherwise it will reduce the saturation magnetization intensity of the alloy soft magnetic.

[0017] Preferably, the heteroatom elements include phosphorus and / or boron.

[0018] Preferably, the passivation layer comprises a phosphating passivation layer.

[0019] Preferably, the material of the insulating coating layer includes phosphate.

[0020] Preferably, the phosphate comprises aluminum dihydrogen phosphate.

[0021] Preferably, the mass ratio of the modified alloy soft magnetic core material, the passivation layer and the insulating coating layer is 100:(0.5-3.0):(2.0-6.0), preferably 100:0.6:2.0, for example, it can be 100:0.5:2.0, 100:0.8:2.2, 100:1.0:2.5, 100:1.2:2.8, 100:1.5:3.0, 100:1.8:3.2, 100:2.0:3.5, 100:2.2:3.8, 100:2.5:4.0, 100:2.8:4.2, 100:3.0:4.5, 100:1.5:4.8, 100:2.0:5.0, 100:3.0:6.0, etc.

[0022] In the present invention, by adjusting the mass ratio of the modified alloy soft magnetic core material, the passivation layer and the insulating coating layer, the prepared alloy soft magnetic composite material with a core-shell structure has the advantages of high insulation resistance and high saturation magnetization, while reducing its total loss at high temperature. If the mass ratio of the modified alloy soft magnetic core material, the passivation layer and the insulating coating layer is relatively low, the total loss of the alloy soft magnetic composite material with a core-shell structure at high temperature will be increased, and vice versa, the saturation magnetization of the alloy soft magnetic composite material with a core-shell structure will be reduced, and its total loss at high temperature will be increased.

[0023] In a second aspect, the present invention provides a method for preparing the alloy soft magnetic composite material with a core-shell structure according to the first aspect, the method comprising the following steps:

[0024] S1. The alloy precursor material and the dopant containing heteroatom elements are smelted to obtain a mixed metal liquid; and then the mixed metal liquid is subjected to gas atomization treatment to obtain a modified alloy soft magnetic core material;

[0025] S2. The modified alloy soft magnetic core material obtained in step S1 is mixed with a passivating agent to obtain a passivated half-step precursor material;

[0026] S3. The half-step precursor material obtained in step S2 and the insulating agent are mixed to obtain a precursor material;

[0027] S4. Pressing the precursor material obtained in step S3 into a ring and subjecting it to heat treatment to obtain the alloy soft magnetic composite material with a core-shell structure.

[0028] Preferably, the preparation method of the modified alloy soft magnetic core material in step S1 includes the following steps: 84.0wt.% to 85.5wt.% of pure iron, 7.4wt.% to 9.4wt.% of pure silicon, 6wt.% to 6.8wt.% of pure aluminum and 0.1wt.% to 0.2wt.% of dopants containing heteroatom elements are smelted into liquid mixed metal liquid, and then the liquid mixed metal liquid is atomized and cooled into powder by spray powder making equipment to obtain the modified alloy soft magnetic core material.

[0029] Preferably, the dopant containing heteroatom elements in step S1 includes iron boride and / or iron phosphide.

[0030] Preferably, the particle size of the modified alloy soft magnetic core material in step S1 is not higher than 200 mesh, preferably 200 mesh.

[0031] Preferably, the heteroatom elements in step S1 include phosphorus and / or boron.

[0032] Preferably, the passivating agent in step S2 includes a phosphoric acid solution.

[0033] Preferably, based on the total mass of the modified alloy soft magnetic core material as 100%, the mass percentage of the solute in the passivator in step S2 is 0.5wt.% to 3wt.%, preferably 0.6wt.% to 1.0wt.%, for example, it can be 0.5wt.%, 0.6wt.%, 0.7wt.%, 0.8wt.%, 0.9wt.%, 1.0wt.%, 1.2wt.%, 1.5wt.%, 1.8wt.%, 2.0wt.%, 2.2wt.%, 2.5wt.%, 2.8wt.%, 3.0wt.%, etc. The present invention makes the alloy soft magnetic composite material have high insulation resistance by regulating the mass percentage of the solute in the passivator.

[0034] Preferably, the insulating agent in step S3 comprises a phosphate solution.

[0035] Preferably, the phosphate solution comprises aluminum dihydrogen phosphate solution.

[0036] Preferably, based on the total mass of the modified alloy soft magnetic core material as 100%, the mass percentage of the solute in the insulating agent in step S3 is 2wt.% to 6wt.%, preferably 2wt.% to 3wt.%, for example, 2wt.%, 2.2wt.%, 2.5wt.%, 2.8wt.%, 3wt.%, 4wt.%, 5wt.%, 6wt.%, etc. The present invention makes the insulating agent easy to disperse by regulating the mass percentage of the solute in the insulating agent, and can achieve the purpose of coating uniformity for the modified alloy soft magnetic core material.

[0037] Preferably, the pressure for pressing into a ring in step S4 is 1500-2000 MPa, for example, 1500 MPa, 1600 MPa, 1700 MPa, 1800 MPa, 1900 MPa, 2000 MPa, etc.

[0038] Preferably, the temperature of the heat treatment in step S4 is 700-850°C, for example, it can be 700°C, 720°C, 750°C, 780°C, 800°C, 820°C, 850°C, etc.; the time is 30-40min, for example, it can be 30min, 32min, 35min, 38min, 40min, etc.

[0039] In a third aspect, the present invention provides an application of the alloy soft magnetic composite material with a core-shell structure according to the first aspect in an inductor magnetic core.

[0040] Compared with the prior art, the present invention has the following beneficial effects:

[0041] The present invention provides an alloy soft magnetic composite material with a core-shell structure. On the one hand, the present invention adjusts the specific composition of the alloy soft magnetic core material and uses heteroatom elements for doping to change the anisotropy field of the magnetocrystalline, thereby improving the inductance (magnetic permeability) working temperature of the alloy soft magnetic material, and finally can change the trend that the high-frequency eddy current loss of the common alloy soft magnetic powder core increases with the increase of the working temperature, so that it has lower eddy current loss and hysteresis loss at a higher working temperature, so that the overall efficiency of the prepared device is maintained at a higher level; on the other hand, the present invention uses materials with good high temperature resistance and insulation to insulate and coat the alloy soft magnetic core material respectively, so that the alloy soft magnetic composite material is easy to form, and then realizes the preparation of the high temperature resistant and low loss alloy magnetic powder core, and finally effectively reduces the total loss at high temperature, changes its trend that the loss increases after the working temperature rises, and then ensures the efficiency of the prepared device.

[0042] The high temperature resistant and insulating material provided by the present invention has good compatibility with the modified alloy soft magnetic core material, and the preparation process is simple and the operation is convenient, thereby improving the production efficiency of the alloy soft magnetic composite material. DETAILED DESCRIPTION

[0043] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0044] In view of the technical problem that the total loss of the sendust metal powder core at high temperature in the prior art increases continuously with the increase of the operating temperature, which will further aggravate the rate of temperature rise and can only be stopped when thermal equilibrium is established, but the current operating temperature of the sendust metal powder core is generally only 80-100°C, and its total loss increases by more than 30% compared with that in the room temperature environment, which makes the efficiency of the prepared device significantly reduced, resulting in a large amount of energy waste. The present invention provides an alloy soft magnetic composite material with a core-shell structure, which has good high temperature resistance and insulation performance and has low loss at high temperature, so as to further improve the use efficiency of the prepared device, and is illustrated in conjunction with the following embodiments.

[0045] Example 1

[0046] The present embodiment provides an alloy soft magnetic composite material with a core-shell structure. The alloy soft magnetic composite material with a core-shell structure includes, from the inside to the outside, a modified alloy soft magnetic core material with a mass ratio of 100:0.6:2.0, a phosphating passivation layer, and an aluminum dihydrogen phosphate insulating coating layer; the modified alloy soft magnetic core material is an alloy soft magnetic core material doped with phosphorus.

[0047] Wherein, taking the total mass of the modified alloy soft magnetic core material as 100%, the modified alloy soft magnetic core material includes 84.4wt.% of iron element, 9.4wt.% of silicon element, 6% of aluminum element and 0.2wt.% of phosphorus element in mass percentages respectively.

[0048] This embodiment also provides a method for the above alloy soft magnetic composite material with a core-shell structure, the method comprising the following steps:

[0049] S1. According to the formula, pure iron, pure silicon, pure aluminum and iron phosphide dopants are smelted into a liquid mixed metal liquid, and then the liquid mixed metal liquid is atomized and cooled into powder using a spray powder making device to obtain a particle size of 200 mesh modified alloy soft magnetic core material;

[0050] S2. 1 kg of the modified alloy soft magnetic core material obtained in step S1 and 17 g of phosphoric acid solution are mixed and introduced into a rotary kiln for heating and drying. The water content in the detection system is less than 0.5% within 10 minutes, wherein the mass percentage of phosphoric acid in the phosphoric acid solution is 1.7 wt.%, to obtain a passivated half-step precursor material;

[0051] S3. The half-step precursor material obtained in step S2 and 60 g of aluminum dihydrogen phosphate solution are mixed, and the mixture is stirred and heated in a rotary kiln until the moisture content in the test system is lower than 0.5%, and the mass percentage of the solute in the aluminum dihydrogen phosphate solution is 6 wt.%, to obtain a precursor material;

[0052] S4. Evenly mix 1 kg of the precursor material obtained in step S3 and 4 g of zinc stearate lubricant, and press them into a ring (26.9 mm OD × 14.7 mm ID × 11.2 mm Ht) under a pressure of 1700 MPa; then heat treat the magnetic ring at 710 ° C and a nitrogen atmosphere for 30 min, and control the temperature rise and treatment time to not exceed 150 min in total, to obtain the alloy soft magnetic composite magnetic ring material with a core-shell structure.

[0053] The alloy soft magnetic composite magnetic ring material with a core-shell structure provided in Example 1 was tested, and the test method was as follows:

[0054] The performance test of the magnetic ring material winding provided in Example 1 was carried out. The primary coil and the secondary coil each had 25 turns. The inductance of multiple magnetic ring materials was tested by an LCR CH3303 model inductor to be 49.5 (±5%) μH, which was converted into a magnetic permeability of 60 μ (±5%). An AC BH meter and an incubator were used to measure the loads of 50 mT and 100 mT respectively at a frequency of 100 kHz. The average total loss at room temperature and the total loss at high temperature (unit: mW / cm 3 ).

[0055] The test results are shown in Table 1:

[0056] Table 1

[0057]

[0058] Example 2

[0059] The present embodiment provides an alloy soft magnetic composite material with a core-shell structure. The alloy soft magnetic composite material with a core-shell structure includes, from the inside to the outside, a modified alloy soft magnetic core material with a mass ratio of 100:0.6:2.0, a phosphating passivation layer, and an aluminum dihydrogen phosphate insulating coating layer; the modified alloy soft magnetic core material is an alloy soft magnetic core material doped with phosphorus.

[0060] Wherein, taking the total mass of the modified alloy soft magnetic core material as 100%, the modified alloy soft magnetic core material includes 84.4wt.% of iron element, 9.4wt.% of silicon element, 6% of aluminum element and 0.2wt.% of phosphorus element in mass percentages respectively.

[0061] This embodiment also provides a method for the above alloy soft magnetic composite material with a core-shell structure, the method comprising the following steps:

[0062] S1. According to the formula, pure iron, pure silicon, pure aluminum and iron phosphide dopants are smelted into a liquid mixed metal liquid, and then the liquid mixed metal liquid is atomized and cooled into powder using a spray powder making device to obtain a particle size of 200 mesh modified alloy soft magnetic core material;

[0063] S2. 500 g of the modified alloy soft magnetic core material obtained in step S1 and 6.5 g of phosphoric acid solution are mixed and introduced into a rotary kiln for heating and drying. The moisture content in the detection system is less than 0.5% within 10 minutes, wherein the mass percentage of phosphoric acid in the phosphoric acid solution is 1.3 wt.%, to obtain a passivated half-step precursor material;

[0064] S3. The half-step precursor material obtained in step S2 and 20 g of aluminum dihydrogen phosphate solution were mixed, and continued to be stirred and heated in a rotary kiln to dry. After the moisture content in the test system was lower than 0.5%, the mass percentage of the solute in the aluminum dihydrogen phosphate solution was 4 wt.%, to obtain a precursor material;

[0065] S4. Evenly mix 500 g of the precursor material obtained in step S3 and 2 g of zinc stearate lubricant, and press them into a ring (26.9 mm OD × 14.7 mm ID × 11.2 mm Ht) under a pressure of 1800 MPa; then heat treat the magnetic ring at 710 ° C and a nitrogen atmosphere for 30 min, and control the temperature rise and treatment time to not exceed 150 min in total, to obtain the alloy soft magnetic composite magnetic ring material with a core-shell structure.

[0066] The alloy soft magnetic composite magnetic ring material with a core-shell structure provided in Example 2 was tested, and the test method was as follows:

[0067] The performance test of the winding of the magnetic ring material provided in Example 2 was carried out. The primary coil and the secondary coil each had 25 turns. The inductance of multiple magnetic ring materials was tested by an LCR CH3303 model inductor to be 49.5 (±5%) μH, which was converted into a magnetic permeability of 60 μ (±5%). An AC BH meter and an incubator were used to measure the loads of 50 mT and 100 mT at a frequency of 100 kHz. The average total loss at room temperature and the total loss at high temperature (unit: mW / cm 3 ).

[0068] The test results are shown in Table 2:

[0069] Table 2

[0070]

[0071] Example 3

[0072] The present embodiment provides an alloy soft magnetic composite material with a core-shell structure. The alloy soft magnetic composite material with a core-shell structure includes, from the inside to the outside, a modified alloy soft magnetic core material with a mass ratio of 100:1.5:4.0, a phosphating passivation layer, and an aluminum dihydrogen phosphate insulating coating layer; the modified alloy soft magnetic core material is an alloy soft magnetic core material doped with phosphorus.

[0073] Among them, taking the total mass of the modified alloy soft magnetic core material as 100%, the modified alloy soft magnetic core material includes 84.5wt.% of iron element, 9.0wt.% of silicon element, 6.35wt.% of aluminum element and 0.15wt.% of phosphorus element in mass percentage respectively.

[0074] This embodiment also provides a method for the above alloy soft magnetic composite material with a core-shell structure, the method comprising the following steps:

[0075] S1. According to the formula, pure iron, pure silicon, pure aluminum and iron phosphide dopants are smelted into a liquid mixed metal liquid, and then the liquid mixed metal liquid is atomized and cooled into powder using a spray powder making device to obtain a particle size of 200 mesh modified alloy soft magnetic core material;

[0076] S2. 1 kg of the modified alloy soft magnetic core material obtained in step S1 and 17 g of phosphoric acid solution are mixed and introduced into a rotary kiln for heating and drying. The water content in the detection system is less than 0.5% within 10 minutes, wherein the mass percentage of phosphoric acid in the phosphoric acid solution is 1.7 wt.%, to obtain a passivated half-step precursor material;

[0077] S3. The half-step precursor material obtained in step S2 and 60 g of aluminum dihydrogen phosphate solution are mixed, and the mixture is stirred and heated in a rotary kiln until the moisture content in the test system is lower than 0.5%, and the mass percentage of the solute in the aluminum dihydrogen phosphate solution is 6 wt.%, to obtain a precursor material;

[0078] S4. Evenly mix 1 kg of the precursor material obtained in step S3 and 4 g of zinc stearate lubricant, and press them into a ring (26.9 mm OD × 14.7 mm ID × 11.2 mm Ht) under a pressure of 1700 MPa; then heat treat the magnetic ring at 710 ° C and a nitrogen atmosphere for 30 min, and control the temperature rise and treatment time to not exceed 150 min in total, to obtain the alloy soft magnetic composite magnetic ring material with a core-shell structure.

[0079] The alloy soft magnetic composite magnetic ring material with a core-shell structure provided in Example 3 was tested, and the test method was as follows:

[0080] The performance test of the magnetic ring material winding provided in Example 3 was carried out. The primary coil and the secondary coil each had 25 turns. The inductance of multiple magnetic ring materials was tested by an LCR CH3303 model inductor to be 49.5 (±5%) μH, which was converted into a magnetic permeability of 60 μ (±5%). An AC BH meter and an incubator were used to measure the loads of 50 mT and 100 mT at a frequency of 100 kHz. The average total loss at room temperature and the total loss at high temperature (unit: mW / cm 3 ).

[0081] The test results are shown in Table 3:

[0082] Table 3

[0083]

[0084] Example 4

[0085] The present embodiment provides an alloy soft magnetic composite material with a core-shell structure. The alloy soft magnetic composite material with a core-shell structure includes, from the inside to the outside, a modified alloy soft magnetic core material with a mass ratio of 100:3.0:6.0, a phosphating passivation layer, and an aluminum dihydrogen phosphate insulating coating layer; the modified alloy soft magnetic core material is an alloy soft magnetic core material doped with phosphorus.

[0086] Wherein, taking the total mass of the modified alloy soft magnetic core material as 100%, the modified alloy soft magnetic core material includes 85.5wt.% of iron element, 7.7wt.% of silicon element, 6.7wt.% of aluminum element and 0.1wt.% of phosphorus element in mass percentage respectively.

[0087] This embodiment also provides a method for the above alloy soft magnetic composite material with a core-shell structure, the method comprising the following steps:

[0088] S1. According to the formula, pure iron, pure silicon, pure aluminum and iron phosphide dopants are smelted into a liquid mixed metal liquid, and then the liquid mixed metal liquid is atomized and cooled into powder using a spray powder making device to obtain a particle size of 200 mesh modified alloy soft magnetic core material;

[0089] S2. 1 kg of the modified alloy soft magnetic core material obtained in step S1 and 17 g of phosphoric acid solution are mixed and introduced into a rotary kiln for heating and drying. The moisture content in the detection system is less than 0.5% within 10 minutes, wherein the mass percentage of phosphoric acid in the phosphoric acid solution is 0.6 wt.%, to obtain a passivated half-step precursor material;

[0090] S3. The half-step precursor material obtained in step S2 and 60 g of aluminum dihydrogen phosphate solution are mixed, and the mixture is stirred and heated in a rotary kiln until the moisture content in the test system is lower than 0.5%, and the mass percentage of the solute in the aluminum dihydrogen phosphate solution is 2 wt.%, to obtain a precursor material;

[0091] S4. Evenly mix 1 kg of the precursor material obtained in step S3 and 4 g of zinc stearate lubricant, and press them into a ring (26.9 mm OD × 14.7 mm ID × 11.2 mm Ht) under a pressure of 1700 MPa; then heat treat the magnetic ring at 710 ° C and a nitrogen atmosphere for 30 min, and control the temperature rise and treatment time to not exceed 150 min in total, to obtain the alloy soft magnetic composite magnetic ring material with a core-shell structure.

[0092] The alloy soft magnetic composite magnetic ring material with a core-shell structure provided in Example 4 was tested, and the test method was as follows:

[0093] The performance test of the magnetic ring material winding provided in Example 4 was carried out. The primary coil and the secondary coil each had 25 turns. The inductance of multiple magnetic ring materials was tested by an LCR CH3303 model inductor to be 49.5 (±5%) μH, which was converted into a magnetic permeability of 60 μ (±5%). An AC BH meter and an incubator were used to measure the loads of 50 mT and 100 mT at a frequency of 100 kHz. The average total loss at room temperature and the total loss at high temperature (unit: mW / cm 3 ).

[0094] The test results are shown in Table 4:

[0095] Table 4

[0096]

[0097]

[0098] Example 5

[0099] The present embodiment provides an alloy soft magnetic composite material with a core-shell structure. The alloy soft magnetic composite material with a core-shell structure includes, from the inside to the outside, a modified alloy soft magnetic core material with a mass ratio of 100:3.0:6.0, a phosphating passivation layer, and an aluminum dihydrogen phosphate insulating coating layer; the modified alloy soft magnetic core material is an alloy soft magnetic core material doped with phosphorus.

[0100] Wherein, taking the total mass of the modified alloy soft magnetic core material as 100%, the modified alloy soft magnetic core material includes 85.5wt.% of iron element, 7.7wt.% of silicon element, 6.7wt.% of aluminum element and 0.1wt.% of phosphorus element in mass percentage respectively.

[0101] This embodiment also provides a method for the above alloy soft magnetic composite material with a core-shell structure, the method comprising the following steps:

[0102] S1. According to the formula, pure iron, pure silicon, pure aluminum and iron phosphide dopants are smelted into a liquid mixed metal liquid, and then the liquid mixed metal liquid is atomized and cooled into powder using a spray powder making device to obtain a particle size of 200 mesh modified alloy soft magnetic core material;

[0103] S2. 1 kg of the modified alloy soft magnetic core material obtained in step S1 and 17 g of phosphoric acid solution are mixed and introduced into a rotary kiln for heating and drying. The moisture content in the detection system is less than 0.5% within 10 minutes, wherein the mass percentage of phosphoric acid in the phosphoric acid solution is 1.0 wt.%, to obtain a passivated half-step precursor material;

[0104] S3. The half-step precursor material obtained in step S2 and 60 g of aluminum dihydrogen phosphate solution are mixed, and the mixture is stirred and heated in a rotary kiln until the moisture content in the test system is lower than 0.5%, and the mass percentage of the solute in the aluminum dihydrogen phosphate solution is 3 wt.%, to obtain a precursor material;

[0105] S4. Evenly mix 1 kg of the precursor material obtained in step S3 and 4 g of zinc stearate lubricant, and press them into a ring (26.9 mm OD × 14.7 mm ID × 11.2 mm Ht) under a pressure of 1700 MPa; then heat treat the magnetic ring at 710 ° C and a nitrogen atmosphere for 30 min, and control the temperature rise and treatment time to not exceed 150 min in total, to obtain the alloy soft magnetic composite magnetic ring material with a core-shell structure.

[0106] The alloy soft magnetic composite magnetic ring material with a core-shell structure provided in Example 5 was tested, and the test method was as follows:

[0107] The performance test of the magnetic ring material winding provided in Example 5 was carried out. The primary coil and the secondary coil each had 25 turns. The inductance of multiple magnetic ring materials was tested by an LCR CH3303 model inductor to be 49.5 (±5%) μH, which was converted into a magnetic permeability of 60 μ (±5%). An AC BH meter and an incubator were used to measure the loads of 50 mT and 100 mT at a frequency of 100 kHz. The average total loss at room temperature and the total loss at high temperature (unit: mW / cm 3 ).

[0108] The test results are shown in Table 5:

[0109] Table 5

[0110]

[0111] Example 6

[0112] The difference between this embodiment and embodiment 1 is that, based on the total mass of the modified alloy soft magnetic core material being 100%, the modified alloy soft magnetic core material comprises 84.4wt.% of iron, 9.4wt.% of silicon, 6.15% of aluminum and 0.05wt.% of phosphorus by mass percentage, and the rest are the same as in embodiment 1;

[0113] The test results are shown in Table 6:

[0114] Table 6

[0115]

[0116] Example 7

[0117] The difference between this embodiment and embodiment 1 is that, based on the total mass of the modified alloy soft magnetic core material being 100%, the modified alloy soft magnetic core material comprises 84.4wt.% of iron, 9.2wt.% of silicon, 6% of aluminum and 0.4wt.% of phosphorus by mass percentage, and the rest are the same as those in embodiment 1;

[0118] The test results are shown in Table 7:

[0119] Table 7

[0120]

[0121] Example 8

[0122] The present embodiment provides an alloy soft magnetic composite material with a core-shell structure. The alloy soft magnetic composite material with a core-shell structure includes, from the inside to the outside, a modified alloy soft magnetic core material, an oxide passivation layer, and an aluminum dihydrogen phosphate insulating coating layer in a mass ratio of 100:0.6:2.0; the modified alloy soft magnetic core material is an alloy soft magnetic core material doped with phosphorus.

[0123] Wherein, taking the total mass of the modified alloy soft magnetic core material as 100%, the modified alloy soft magnetic core material includes 84.4wt.% of iron element, 9.4wt.% of silicon element, 6% of aluminum element and 0.2wt.% of phosphorus element in mass percentages respectively.

[0124] This embodiment also provides a method for the above alloy soft magnetic composite material with a core-shell structure, the method comprising the following steps:

[0125] S1. According to the formula, pure iron, pure silicon, pure aluminum and iron phosphide dopants are smelted into a liquid mixed metal liquid, and then the liquid mixed metal liquid is atomized and cooled into powder using a spray powder making device to obtain a particle size of 200 mesh modified alloy soft magnetic core material;

[0126] S2. 1kg and 8gK of the modified alloy soft magnetic core material obtained in step S1 0.8 (Al,Fe,Mg) 2 (SiAl) 4 O 10 (OH) 2 The mineral powder (particle size is 1600 mesh) is mixed and introduced into a rotary kiln for heating and drying to obtain a passivated half-step precursor material;

[0127] S3. The half-step precursor material obtained in step S2 and 60 g of aluminum dihydrogen phosphate solution are mixed, and the mixture is stirred and heated in a rotary kiln until the moisture content in the test system is lower than 0.5%, and the mass percentage of the solute in the aluminum dihydrogen phosphate solution is 6 wt.%, to obtain a precursor material;

[0128] S4. Evenly mix 1 kg of the precursor material obtained in step S3 and 4 g of zinc stearate lubricant, and press them into a ring (26.9 mm OD × 14.7 mm ID × 11.2 mm Ht) under a pressure of 1700 MPa; then heat treat the magnetic ring at 710 ° C and a nitrogen atmosphere for 30 min, and control the temperature rise and treatment time to not exceed 150 min in total, to obtain the alloy soft magnetic composite magnetic ring material with a core-shell structure.

[0129] The alloy soft magnetic composite magnetic ring material with a core-shell structure provided in Example 8 was tested, and the test method was as follows:

[0130] The performance test of the magnetic ring material winding provided in Example 8 was carried out. The primary coil and the secondary coil each had 25 turns. The inductance of multiple magnetic ring materials was tested by an LCR CH3303 model inductor to be 49.5 (±5%) μH, which was converted into a magnetic permeability of 60 μ (±5%). An AC BH meter and an incubator were used to measure the loads of 50 mT and 100 mT at a frequency of 100 kHz. The average total loss at room temperature and the total loss at high temperature (unit: mW / cm 3 ).

[0131] The test results are shown in Table 8:

[0132] Table 8

[0133]

[0134] Example 9

[0135] The present embodiment provides an alloy soft magnetic composite material with a core-shell structure. The alloy soft magnetic composite material with a core-shell structure includes, from the inside to the outside, a modified alloy soft magnetic core material with a mass ratio of 100:0.6:2.0, a phosphating passivation layer, and a silicone resin insulating coating layer; the modified alloy soft magnetic core material is an alloy soft magnetic core material doped with phosphorus.

[0136] Wherein, taking the total mass of the modified alloy soft magnetic core material as 100%, the modified alloy soft magnetic core material includes 84.4wt.% of iron element, 9.4wt.% of silicon element, 6% of aluminum element and 0.2wt.% of phosphorus element in mass percentages respectively.

[0137] This embodiment also provides a method for the above alloy soft magnetic composite material with a core-shell structure, the method comprising the following steps:

[0138] S1. According to the formula, pure iron, pure silicon, pure aluminum and iron phosphide dopants are smelted into a liquid mixed metal liquid, and then the liquid mixed metal liquid is atomized and cooled into powder using a spray powder making device to obtain a particle size of 200 mesh modified alloy soft magnetic core material;

[0139] S2. 1 kg of the modified alloy soft magnetic core material obtained in step S1 and 17 g of phosphoric acid solution are mixed and introduced into a rotary kiln for heating and drying. The water content in the detection system is less than 0.5% within 10 minutes, wherein the mass percentage of phosphoric acid in the phosphoric acid solution is 1.7 wt.%, to obtain a passivated half-step precursor material;

[0140] S3. The half-step precursor material obtained in step S2 and 12 g of a silicone resin were mixed and continued to stir and heat and dry in a rotary kiln to obtain a precursor material;

[0141] S4. Evenly mix 1 kg of the precursor material obtained in step S3 and 4 g of zinc stearate lubricant, and press them into a ring (26.9 mm OD × 14.7 mm ID × 11.2 mm Ht) under a pressure of 1700 MPa; then heat treat the magnetic ring at 710 ° C and a nitrogen atmosphere for 30 min, and control the temperature rise and treatment time to not exceed 150 min in total, to obtain the alloy soft magnetic composite magnetic ring material with a core-shell structure.

[0142] The alloy soft magnetic composite magnetic ring material with a core-shell structure provided in Example 9 was tested, and the testing method was as follows:

[0143] The performance test of the magnetic ring material winding provided in Example 9 was carried out. The primary coil and the secondary coil each had 25 turns. The inductance of multiple magnetic ring materials was tested by an LCR CH3303 model inductor to be 49.5 (±5%) μH, which was converted into a magnetic permeability of 60 μ (±5%). An AC BH meter and an incubator were used to measure the loads of 50 mT and 100 mT at a frequency of 100 kHz. The average total loss at room temperature and the total loss at high temperature (unit: mW / cm 3 ).

[0144] The test results are shown in Table 9:

[0145] Table 9

[0146]

[0147] Comparative Example 1

[0148] This comparative example provides an alloy soft magnetic composite material with a core-shell structure, which comprises, from the inside to the outside, an alloy soft magnetic core material, a phosphating passivation layer, and an aluminum dihydrogen phosphate insulating coating layer in a mass ratio of 100:0.6:2.0.

[0149] Wherein, taking the total mass of the alloy soft magnetic core material as 100%, the alloy soft magnetic core material includes 85.0wt.% of iron element, 9.6wt.% of silicon element and 5.4% of aluminum element in mass percentages respectively.

[0150] This comparative example also provides a method for the above-mentioned alloy soft magnetic composite material with a core-shell structure, the method comprising the following steps:

[0151] S1. According to the formula, 85.0wt.% of pure iron, 9.6wt.% of pure silicon and 5.4% of pure aluminum are melted into a liquid mixed metal liquid, and then the liquid mixed metal liquid is atomized and cooled into powder using a spray powder making equipment to obtain a soft magnetic alloy core material with a particle size of 200 mesh;

[0152] S2. 1 kg of the alloy soft magnetic core material obtained in step S1 and 17 g of phosphoric acid solution are mixed and introduced into a rotary kiln for heating and drying. The moisture content in the detection system is less than 0.5% within 10 minutes, wherein the mass percentage of phosphoric acid in the phosphoric acid solution is 1.7 wt.%, to obtain a passivated half-step precursor material;

[0153] S3. The half-step precursor material obtained in step S2 and 60 g of aluminum dihydrogen phosphate solution are mixed, and the mixture is stirred and heated in a rotary kiln until the moisture content in the test system is lower than 0.5%, and the mass percentage of the solute in the aluminum dihydrogen phosphate solution is 6 wt.%, to obtain a precursor material;

[0154] S4. Evenly mix 1 kg of the precursor material obtained in step S3 and 4 g of zinc stearate lubricant, and press them into a ring (26.9 mm OD × 14.7 mm ID × 11.2 mm Ht) under a pressure of 1700 MPa; then heat treat the magnetic ring at 710 ° C and a nitrogen atmosphere for 30 min, and control the temperature rise and treatment time to not exceed 150 min in total, to obtain the alloy soft magnetic composite magnetic ring material with a core-shell structure.

[0155] The alloy soft magnetic composite magnetic ring material with a core-shell structure provided in Comparative Example 1 was tested, and the test method was as follows:

[0156] The performance test of the magnetic ring material winding provided in Comparative Example 1 was carried out. The primary coil and the secondary coil had 25 turns each. The inductance of multiple magnetic ring materials was tested by LCR CH3303 model inductance meter to be 49.5 (±5%) μH, which was converted into a magnetic permeability of 60μ (±5%). The AC BH meter and the heat preservation box were used to measure the loads of 50mT and 100mT respectively at a frequency of 100kHz. The average total loss at room temperature and the total loss at high temperature (unit: mW / cm 3 ).

[0157] The test results are shown in Table 10:

[0158] Table 10

[0159]

[0160] In summary, the present invention adjusts the specific composition of the alloy soft magnetic core material and uses heteroatom elements to dope to change the anisotropy field of the magnetic crystal, thereby improving the inductance (magnetic permeability) working temperature of the alloy soft magnetic material, and uses materials with good high temperature resistance and insulation properties to insulate and coat the alloy soft magnetic core material, thereby effectively reducing the total loss at high temperature and changing the trend of increasing loss as the working temperature rises, thereby ensuring the efficiency of the prepared device.

[0161] The applicant declares that the present invention illustrates the process method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned process steps, that is, it does not mean that the present invention must rely on the above-mentioned process steps to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. An alloy soft magnetic composite material with a core-shell structure, characterized in that: The alloy soft magnetic composite material with a core-shell structure comprises, from the inside to the outside, a modified alloy soft magnetic core material, a passivation layer and an insulating coating layer; The modified alloy soft magnetic core material is an alloy soft magnetic core material doped with heteroatom elements.

2. The alloy soft magnetic composite material with a core-shell structure according to claim 1, characterized in that: Taking the total mass of the modified alloy soft magnetic core material as 100%, the modified alloy soft magnetic core material includes 84.0wt.% to 85.5wt.% of iron, 7.4wt.% to 9.4wt.% of silicon, 6wt.% to 6.8wt.% of aluminum and 0.1wt.% to 0.2wt.% of heteroatoms, preferably 84.4wt.% to 84.5wt.% of iron, 9.4wt.% of silicon, 6% of aluminum and 0.2wt.% of heteroatoms; Preferably, the heteroatom elements include phosphorus and / or boron.

3. The alloy soft magnetic composite material with a core-shell structure according to claim 1 or 2, characterized in that: The passivation layer comprises a phosphating passivation layer; Preferably, the material of the insulating coating layer includes phosphate; Preferably, the phosphate comprises aluminum dihydrogen phosphate.

4. The alloy soft magnetic composite material with a core-shell structure according to any one of claims 1 to 3, characterized in that: The mass ratio of the modified alloy soft magnetic core material, the passivation layer and the insulating coating layer is 100:(0.5-3.0):(2.0-6.0), preferably 100:0.6:2.

0.

5. A method for preparing an alloy soft magnetic composite material with a core-shell structure according to any one of claims 1 to 4, characterized in that: The method comprises the following steps: S1. The alloy precursor material and the dopant containing heteroatom elements are smelted to obtain a mixed metal liquid; and then the mixed metal liquid is subjected to gas atomization treatment to obtain a modified alloy soft magnetic core material; S2. The modified alloy soft magnetic core material obtained in step S1 is mixed with a passivating agent to obtain a passivated half-step precursor material; S3. The half-step precursor material obtained in step S2 and the insulating agent are mixed to obtain a precursor material; S4. Pressing the precursor material obtained in step S3 into a ring and subjecting it to heat treatment to obtain the alloy soft magnetic composite material with a core-shell structure.

6. The method according to claim 5, characterized in that The preparation method of the modified alloy soft magnetic core material in step S1 comprises the following steps: 84.0wt.% to 85.5wt.% of pure iron, 7.4wt.% to 9.4wt.% of pure silicon, 6wt.% to 6.8wt.% of pure aluminum and 0.1wt.% to 0.2wt.% of a dopant containing heteroatom elements are melted into a liquid mixed metal liquid, and then the liquid mixed metal liquid is atomized and cooled into powder by a spray powder making device to obtain the modified alloy soft magnetic core material; Preferably, the dopant containing heteroatom elements in step S1 includes iron boride and / or iron phosphide; Preferably, the particle size of the modified alloy soft magnetic core material in step S1 is not higher than 200 mesh, preferably 200 mesh.

7. The method according to claim 5 or 6, characterized in that: The heteroatom elements in step S1 include phosphorus and / or boron.

8. The method according to any one of claims 5 to 7, characterized in that: The passivating agent in step S2 includes a phosphoric acid solution; Preferably, based on the total mass of the modified alloy soft magnetic core material as 100%, the mass percentage of the solute in the passivating agent in step S2 is 0.5wt.% to 3wt.%, preferably 0.6wt.% to 1.0wt.%.

9. The method according to any one of claims 5 to 8, characterized in that: In step S3, the insulating agent includes a phosphate solution; Preferably, the phosphate solution comprises aluminum dihydrogen phosphate solution; Preferably, based on the total mass of the modified alloy soft magnetic core material as 100%, the mass percentage of the solute in the insulating agent in step S3 is 2wt.% to 6wt.%, preferably 2wt.% to 3wt.%; Preferably, the pressure for pressing into a ring in step S4 is 1500-2000 MPa; Preferably, the heat treatment in step S4 is performed at a temperature of 700 to 850° C. and for a time of 30 to 40 minutes.

10. Use of the alloy soft magnetic composite material with a core-shell structure according to any one of claims 1 to 4 in an inductor magnetic core.

Citation Information

Patent Citations

  • Iron-silicon-aluminum soft magnetic powder core with high direct-current bias performance and preparation method of iron-silicon-aluminum soft magnetic powder core

    CN111696744A